2023
DOI: 10.1108/nfs-04-2023-0076
|View full text |Cite
|
Sign up to set email alerts
|

This is not my jam: an Italian choice experiment on the influence of typical product attributes on consumers’ willingness to pay

Abstract: Purpose Packaging and labelling have become essential to how food manufacturers generate and deliver value to customers. The information displayed on the packaging can be used to communicate to customers the properties and unique characteristics of a food product (e.g. nutrients, calories and country of origin). To achieve communication goals effectively, manufacturers need to understand how consumers evaluate products based on their attributes. In particular, companies should be aware of which specific produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…, 2020; Meas et al. , 2015), which can be used as a tool to communicate product uniqueness if manufacturers have awareness about how these aspects are evaluated by customers (Boccia et al. , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2020; Meas et al. , 2015), which can be used as a tool to communicate product uniqueness if manufacturers have awareness about how these aspects are evaluated by customers (Boccia et al. , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Packaging can contribute in creating the first impression required to make the brand look different from competing brands (Panda et al, 2022), and it can contribute in brand recognition and positive brand association. Some aspects of packaging that have been considered significant are the shape, colour, shading, content and material, pattern (Buchm€ uller et al, 2022;Chonpracha et al, 2020;Meas et al, 2015), which can be used as a tool to communicate product uniqueness if manufacturers have awareness about how these aspects are evaluated by customers (Boccia et al, 2023). In case of food category, customers cannot taste the product; hence, they have to rely on multiple cues while making their food choice decision (Meas et al, 2015;Odaman et al, 2020;Panda et al, 2022).…”
Section: Packaging Of Rte Productsmentioning
confidence: 99%
“…Many studies have investigated consumers' food safety concerns and differences in their perceptions of information such as origin, production methods and health claims. These studies Consumers' interpretation of food origin have found that consumers would choose food made in traditional methods rather than industrially (Boccia et al, 2024) and that consumers' perceptions and attitudes towards risks are associated with individual characteristics (Buchler et al, 2010;Cheng et al, 2017;Dean et al, 2007). According to a survey among the Japanese people, more women claimed they have knowledge of food safety and that they make their own judgements about food safety, while more young men said they do not (Ministry of Agriculture, Forestry and Fisheries of Japan, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated consumers’ food safety concerns and differences in their perceptions of information such as origin, production methods and health claims. These studies have found that consumers would choose food made in traditional methods rather than industrially (Boccia et al. , 2024) and that consumers’ perceptions and attitudes towards risks are associated with individual characteristics (Buchler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in modern life, people are highly aware about the quality of food they consumed, and interrelationship of environmental factors and its health effects on food products in which this affects the consumers’ concerns on healthier lifestyle and environmental issues and finally on how they select and buy food products based on their perspectives and attitude toward food quality 8 . Recent changes in food and dietary habits in developing nations have attracted a special attention for up-to-date evaluation in food preference and diet behaviors particularly among adolescence.…”
Section: Introductionmentioning
confidence: 99%